2018
DOI: 10.1016/j.scitotenv.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Chesapeake Bay's water quality condition has been recovering: Insights from a multimetric indicator assessment of thirty years of tidal monitoring data

Abstract: To protect the aquatic living resources of Chesapeake Bay, the Chesapeake Bay Program partnership has developed guidance for state water quality standards, which include ambient water quality criteria to protect designated uses (DUs), and associated assessment procedures for dissolved oxygen (DO), water clarity/underwater bay grasses, and chlorophyll-a. For measuring progress toward meeting the respective states' water quality standards, a multimetric attainment indicator approach was developed to estimate com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 39 publications
(49 reference statements)
3
42
0
Order By: Relevance
“…First, Kemp omitted data from years that diverged from average conditions, while 2016 was a dry year. Less discharge, combined with reductions in nitrogen inputs and chlorophyll (Zhang et al, 2018) and nitrogen removal by SAV beds that have grown in area by 50 km 2 since 1998 (Gurbisz and Kemp, 2014;Orth et al, 2017), likely resulted in reduced eutrophication and consequently, lower productivity in the mesohaline and polyhaline regions. So, our net export flux estimates are compatible with the previous organic carbon budget.…”
Section: Discussionmentioning
confidence: 99%
“…First, Kemp omitted data from years that diverged from average conditions, while 2016 was a dry year. Less discharge, combined with reductions in nitrogen inputs and chlorophyll (Zhang et al, 2018) and nitrogen removal by SAV beds that have grown in area by 50 km 2 since 1998 (Gurbisz and Kemp, 2014;Orth et al, 2017), likely resulted in reduced eutrophication and consequently, lower productivity in the mesohaline and polyhaline regions. So, our net export flux estimates are compatible with the previous organic carbon budget.…”
Section: Discussionmentioning
confidence: 99%
“…Testa et al (2018) reported a decline in NH 4 and an increase in NO 2+3 concentrations in channel bottom waters during late summer as dissolved oxygen concentrations have increased, suggesting a vicious biogeochemical cycle may be breaking (Kemp et al, 2005). Zhang et al (2018) demonstrated progressive improvement in a multimetric index of water quality attainment that integrates dissolved oxygen, water clarity, submersed vascular vegetation and chlorophyll a. This began in the late 1990s following wastewater treatment plant upgrades and reductions in atmospheric deposition of nitrogen.…”
Section: Chesapeake Baymentioning
confidence: 99%
“…Excess nutrients can cause hypoxic zones, algal blooms, and fish kills (Boesch et al 2001, Burgin and Hamilton 2007, Perez 2015. Though many parts of the Bay are showing water quality improvement, as of 2016, 58% of Bay tidal waters did not meet standards for dissolved oxygen, chlorophyll a, and water clarity, key indicators of good water quality (Zhang et al 2018). In 2017, the U.S. Geological Survey found increasing N and P loads at several monitoring stations along major tributaries that drain into the Bay (Moyer and Blomquist 2018).…”
Section: Study Sitementioning
confidence: 99%